Preoperative cardiopulmonary exercise testing improves risk assessment of morbidity and length of stay following cytoreductive surgery with hyperthermic intraperitoneal chemotherapy. Issue 6 (November 2022) - Pillinger, Neil L; Koh, Cherry EP; Ansari, Nabila; Munoz, Phillip A; McNamara, Stephen G; Steffens, Daniel
Cytoreductive surgery (CRS) and hyperthermic intraperitoneal chemotherapy (HIPEC) are the standard treatment for selected patients with peritoneal malignancy. The optimal means of assessing risk prior to these complex operations is not known. This study explored the associations between preoperative cardiopulmonary exercise testing (CPET) variables and postoperative outcomes following elective CRS and HIPEC. This study included patients who underwent routine preoperative CPET prior to elective CRS and HIPEC at Royal Prince Alfred Hospital in Sydney between July 2017 and July 2020. CPET was performed using a cycle ergometer and measured peak oxygen uptake (VO 2 peak) and anaerobic threshold (AT). Outcomes included in-hospital morbidity, length of intensive care unit (ICU) stay and hospital stay. The associations between preoperative CPET variables and postoperative morbidity were assessed using univariate and multivariate analyses. A total of 129 patients were included. Mean age was 56 years (standard deviation (SD) 12.5 years), and colorectal cancer was the most common indication for CRS and HIPEC. The overall complication rate was 69%, and two (1.6%) patients died in hospital. Patients who did not develop any postoperative complication had slightly higher preoperative AT and VO 2 peak and shorter length of hospital stay. Data in this study support the role of CPET prior to CRS and HIPEC as an adjunct to improve risk assessment.